The Cconstitutional theory of the federation and the European Union - Larsen, Signe Rehling (Oxford University Press, 2021)
This book departs from the 'statist' imagination by suggesting the EU is a federal union of states, or a federation. Dedicated to the constitutional theory of federalism, this book gives the strengths and weaknesses of a federation as a political form, its histories, and current perils for the EU.